Antara Strategi dan Siasat Misi SVD Distrik Sumut - Lelaona, Yohanes Antonius (Perspektif, 2017)
Based on his personal experiences in North Sumatra, the writer offers in this article some insightful ideas in doing mission and being missionary crossculturally. First of all, every missionary should realise himself as guest in any mission field. What is important for a guest is just learning to know the local people and their cultural values. As a Divine Word Missionary, the writer underlines the legacy of St. Arnold Janssen, the founder of the Society of the Divine Word, namely interculturity. Internally, members of the Society are united from various ethnic groups, languages, and cultures into a fertile and dynamic community. Externally, everybody has been trained and conditioned to be able to adjust himself into any new cultural milieu. Involve in mission such as in North Sumatra, every new missionary is expected to open himself to the Batak culture. To be a good missionary among the Batak, then, one must know quite well the Batak cultural values and speak their language. There is no other strategy for being a good missionary, namely a good preacher, than to first of all be a good learner, a good disciple. That is what exactly means an intercultural person.